„Old age ends in the grave”: A Transgressive Perception of Aging in Rural Culture - Gapiński, Bartłomiej (Requiem, 2025)
The author focuses on examining the relationship between old age and death in folk culture, particularly during the second half of the 19th century (using material from Oskar Kolberg) and the early 20th century. The study focuses on peasant thanatology, particularly the connection between elderly individuals and funeral rituals. The author pays special attention to the social role of the „odpraszacz,” a man who led funeral ceremonies. Although funeral guides existed in all three partitions of Poland, their behaviours are most extensively described in Galicia, not only in ethnographic accounts but also in peasant diaries. These guides served as the voice of the deceased, apologizing on their behalf and speaking as if bearing witness to their presence from the other side. In rural culture, the image of the elderly was associated with the afterlife, and the elderly were seen as guides to the other side. Folk death had its metaphysics and was considered a natural part of life, reflecting God’s will and the necessity of passing on the generational legacy, participating in the relay of generations.